Incorporation of hexa chiloro cyclo triphosphazene onto sago waste - Teng, Jing Xin (Universiti Malaysia Sarawak (UNIMAS), 2010)
Sago waste is kinds of agriculture waste which can be utilize to benefit human being. Modification of sago waste through cooperation with phosphazene gives the properties of fire retardant. The porosity of the modified sago waste results in choice as material for sound absorber panel. Modification of sago waste was done in reflux under nitrogen condition. Molding of modified sago waste with polystyrene and dichloromethane for ignition test. Ignition test using Bunsen Burner shows that modification of sago waste is successful.